Efficacy and safety of IBI351 (fulzerasib) monotherapy in KRASG12C inhibitor-naïve Chinese patients with KRAS G12C-mutated metastatic colorectal cancer: a pooled analysis from phase I part of two studies - Ying Yuan; Yanhong Deng; Yongdong Jin; Zengqing Guo; Yueyin Pan; Cunji Wang; Zhiwu Wang; Yi Hu; Dong Hua; Xiangjiao Meng; Zhiye Zhang; Mingfang Zhao; et al. (Signal Transduction and Targeted Therapy)
Abstract IBI351 (also known as fulzerasib or GFH925), an irreversible covalent inhibitor of KRASG12C, has demonstrated promising anti-tumour activity in patients with solid tumours. In this study, data were pooled from the phase I part of two clinical studies (NCT05005234 and NCT05497336), aiming to evaluate the efficacy and safety of IBI351 monotherapy in KRASG12C inhibitor-naïve Chinese patients with KRAS G12C-mutated metastatic colorectal cancer (CRC). The objective response rate (ORR) was the primary endpoint. Secondary endpoints included disease control rate (DCR), progression-free survival (PFS), and overall survival (OS). As of December 13, 2023, 56 patients treated with IBI351 monotherapy were included. The median duration of treatment was 7.7 months (range: 0.3–16.7). The confirmed ORR was 44.6% (95% CI: 31.3–58.5), with a DCR of 87.5% (95% CI: 75.9–94.8). With a median follow-up of 13.8 months, the median PFS was 8.1 months (95% CI: 5.5–13.8). The median OS was 17.0 months (95% CI: 12.6–not reached). Treatment-related adverse events (TRAEs) occurred in 53 patients (94.6%), with grade 3 TRAEs in 14 patients (25.0%). No grade 4 or 5 TRAEs were observed. The most common grade 3 TRAEs were anaemia (n = 4, 7.1%) and gamma-glutamyltransferase increased (n = 3, 5.4%). TRAEs led to dose interruption in 12 patients (21.4%) and dose reduction in six patients (10.7%). No TRAEs resulted in treatment discontinuation. IBI351 demonstrated encouraging clinical efficacy and a manageable safety profile in KRASG12C inhibitor-naïve Chinese patients with KRAS G12C-mutated metastatic CRC.